2008
DOI: 10.1002/pon.1356
|View full text |Cite
|
Sign up to set email alerts
|

Communicating genetics research results to families: problems arising when the patient participant is deceased

Abstract: Objectives: This study explores communication within families of clinically significant genetics research results, after the death of the patient participant. BRCA2 mutations were found in several men after their death from prostate cancer. Spouses were given the results in a genetic counselling session and asked to inform relatives.Methods: Cross-sectional, qualitative exploratory study. Interviews with 13 relatives, including informers and recipients of the information, were analysed using interpretative phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 38 publications
(58 reference statements)
0
28
0
Order By: Relevance
“…These were: perceived responsibility to tell, relationship type and quality, deciding who to tell, anticipation of relative's reactions, mutation status, and personal feelings. Counsellees believed that they were responsible for disseminating or felt obliged to disseminate genetic risk information [10,21,29] or thought that that relatives had a right to know [13,18,31,34,35]. This was often linked to a belief that the risk information may help prevent disease or aid medical decision-making in relatives [10,13,21,31,35,46].…”
Section: Functions and Influences Of Communication About Genetic Riskmentioning
confidence: 93%
See 1 more Smart Citation
“…These were: perceived responsibility to tell, relationship type and quality, deciding who to tell, anticipation of relative's reactions, mutation status, and personal feelings. Counsellees believed that they were responsible for disseminating or felt obliged to disseminate genetic risk information [10,21,29] or thought that that relatives had a right to know [13,18,31,34,35]. This was often linked to a belief that the risk information may help prevent disease or aid medical decision-making in relatives [10,13,21,31,35,46].…”
Section: Functions and Influences Of Communication About Genetic Riskmentioning
confidence: 93%
“…The review identified four functions of communicating within families about genetic risk: discharging responsibility for informing the family [10,15,29,35,46]; needing to gain emotional support and advice [10,15,34,46];obtaining information from the family [1,15,18]; and preventing illness through telling those at risk of their risk status [10,15,16,29,38,46].…”
Section: Functions and Influences Of Communication About Genetic Riskmentioning
confidence: 99%
“…9 In the context of cancer predisposition, family communication is often a burden for the index case 33 and flawed: hampered by lack of social contact, family rifts and relationship breakdown the quality of information may be poor 20 and compromised by perceived lack of authority of the informing relative. 34 At-risk relatives are frequently left uninformed of conditions that are treatable or for which surveillance is available. With consent of the proband, direct contact has been used for Familial hypercholesterolaemia in the UK and the Netherlands and is accepted by family members, 35 although a recent study finds that family members prefer indirect cascading.…”
Section: Discussionmentioning
confidence: 99%
“…The strong hold of psychological factors on the actions of individuals in the face of scientific information provided through high-quality genetic counseling and testing remains striking. Despite being told by medical professionals of the importance of informing relatives about the presence of a deleterious familial cancer-predisposing mutation, it can take years before such information is conveyed by the tested individuals to some sisters, brothers, adult children, stepchildren, or parents due to psychological hesitancies that take precedence over motivations to altruistically inform [1,2]. Gender also impacts the use and dissemination of genetic information.…”
mentioning
confidence: 99%
“…Koehly et al [3] describe areas of overlap and non-continuity in the knowledge and cancer anxiety felt by sisters. Ormondroyd et al [2] studied dissemination of BRCA1/2 results given to widows or other next of kin of men with prostate cancer who died before their results were available. The complexities of conveying this information to at-risk relatives are described in narratives from the subjects.…”
mentioning
confidence: 99%